Understanding foreign language writing anxiety and its correlates - Li, Rui (Frontiers in Psychology, 2022)
Despite the increasing number of empirical studies that investigated foreign language writing anxiety and its correlates, there is still a lack of quantitative meta-analytic attempt on the effect sizes among these studies. To bridge the gap, this study identified 84 effect sizes from 22 primary studies to meta-analyze the correlations of foreign language writing anxiety and several key high-and low-evidence correlates. For the two high-evidence correlates, moderator analyses were also conducted, which demonstrated that foreign language writing anxiety has a moderate correlation with foreign language writing self-efficacy and foreign language writing performance. The three low-evidence correlates have positively moderate effects of foreign language listening anxiety, foreign language speaking anxiety and foreign language reading anxiety. The significant moderating effects of learners’ age and language proficiency were obtained. With respect to the results, pedagogical implications were discussed as well.